The benefits of Gum Acacia / Hayati Adilin Mohd Abd Majid, Siti Nursharmila Abdullah Rambli and Ruhaya Hussin - Mohd Abd Majid, Hayati Adilin; Abdullah Rambli, Siti Nursharmila; Hussin, Ruhaya (UiTM Cawangan Negeri Sembilan, 2022)
GUM ACACIA (GA) well acknowledged as Gum Arabic is a gum that is gained by making cuts in the bark of the grown trees of acacia Senegal trees. The term "Gum Arabic" originated from the trading between the Arab and European countries. The primary source of the GA is from Kordofan, in the region of Sudan, which yields over 90% of the world's resources, [2]. It is undeniable that Islam et al. (1997) showed that the marketable grade of GA which was composed from Acacia Senegal trees has the best quality as compared to other varieties [3]. GA, chemically is a complex polysaccharide that has been deemed as a safe dietary fibre by the United States, Food and Drug Administration (FDA) since 1970.